Preimenovanje prelaza Ljubelj v Stari Ljubelj - Geršič, Matjaž (Geografski vestnik, 2024)
This article presents the Slovenian geographical name Ljubelj and how its denotations have changed over time,up to the present day, when the name has acquired multiple denotations in spoken and written use, and is thusfunctionally overloaded. The Commission for the Standardization of Geographical Names of the Governmentof the Republic of Slovenia, taking into account an initiative from the Municipality of Tržič, encouraged the prepa-ration of an expert opinion, which is also presented in this ar ticle from a linguistic point of view– that is, fromthe perspective of ononymization (naming) and transonymization (the transfer of a name to another entity).
Keywords: Geografija; geographical names; geography; Ljubelj (Slovenia and Austria; mountain pass); Standardizacija; standardization; Zemljepisna imena